The Covert Sphere : Secrecy, Fiction, and the National Security State - Melley, Timothy, 1963- (Book collections on Project MUSE., 2012)
"In The Covert Sphere, Melley links this cultural shift to the birth of the national security state in 1947. As the United States developed a vast infrastructure of clandestine organizations, it shielded policy from the public sphere and gave rise to a new cultural imaginary, "the covert sphere." One of the surprising consequences of state secrecy is that citizens must rely substantially on fiction to "know," or imagine, their nation's foreign policy. The potent combination of institutional secrecy and public fascination with the secret work of the state was instrumental in fostering the culture of suspicion and uncertainty that has plagued American society ever since--and, Melley argues, that would eventually find its fullest expression in postmodernism. The Covert Sphere traces these consequences from the Korean War through the War on Terror, examining how a regime of psychological operations and covert action has made the conflation of reality and fiction a central feature of both U.S. foreign policy and American culture. Melley interweaves Cold War history with political theory and original readings of films, television dramas, and popular entertainments--from The Manchurian Candidate through 24--as well as influential writing by Margaret Atwood, Robert Coover, Don DeLillo, Joan Didion, E.L. Doctorow, Michael Herr, Denis Johnson, Norman Mailer, Tim O'Brien, and many others."--Publisher's website